(Retrospective analysis of mechanical control activities of Tlfyus serrulatus in Americana, São Paulo state) - Lisboa, Letícia Bernardo [UNESP]; Brites-Neto, José (Universidade Federal do Paraná, 2022)
The epidemiological situation of scorpionism in Brazilian municipalities demonstrates an increasing linear trend with a high probabilistic risk of accidents and deaths. In the city of Americana, data from active search of Tityus serrulatus as a methodology for mechanical control of scorpions, were evaluated in a retrospective analysis from 2006 to 2021. It was demonstrated that this activity contributes to the destination of live specimens for the production of anti-scorpion serum, without presenting efficiency in the control of environmental infestations of these venomous animals. Biological and chemical control measures must be incorporated, through municipal public health policies, with a more adequate level of attention to integrated pest management.
ANÁLISE RETROSPECTIVA DAS ATIVIDADES DE CONTROLE MECÂNICO DE TITYUS SERRULATUS NO MUNICÍPIO DE AMERICANA, SÃO PAULO
Keywords: active search; animais peçonhentos; busca ativa; environmental health; escorpiões; linha de tendência; saúde ambiental; scorpions; tendency line; venomous animals